Study of Meat Species Adulteration in Indonesian Commercial Beef Meatballs Related to Halal Law Implementation - Siswara, Hamzah Nata; Erwanto, Yuny; Suryanto, Edi (Frontiers in Sustainable Food Systems, 2022)
Meatballs are one of the processed meat products that are susceptible to alduteration. Indonesia enforces a halal product guarantee regulation so that all products in circulation must be free from non-halal ingredients. This study aims to detect contamination of pork and chicken with the PCR method on commercial beef meatballs. The samples of commercial meatballs were taken from 36 meatball shops in Bojonegoro Regency, East Java and in Boyolali Regency, Central Java Province, respectively. Reference meatballs as a positive control were prepared in the laboratory. DNA isolation was carried out on commercial sample meatballs, reference meatballs, and 13 species of fresh meat for specificity tests. DNA concentration was measured using a spectrophotometer and visualization of the isolation and PCR results was carried out using agarose gel electrophoresis and UV transilluminator. DNA isolates were amplified by PCR using chicken-specific primers as follows: forward 5' CTG GGT TGA AAA GGA CCA CAG T 3' and reverse 5' GTG ACG CAC TGA ACA GGT TG 3'; bovine : forward 5' TTT CTT GTT ATA GCC CAC CAC AC 3' and reverse 5' TTT CTC TAA AGG TGG TTG GTC AG 3'; Pork: Forward 5' AAA GGA CCC AAC GTT GTA GG 3' and reverse 5' TAG TGC TAG GGA TAA GGC TAG G 3'. The results showed that there was contamination of chicken meat in meatballs labeled with beef meatballs in 30 samples from 36 samples in Bojonegoro Regency and 33 samples from 36 samples in Boyolali Regency. The results also showed that 22 samples of commercial beef meatballs in Boyolali Regency were confirmed containing pork. The implementation of the PCR method using the three specific primers proved the presence of meat contamination that did not match the label on the meatballs circulating in the Indonesian market. Contamination of pork in beef meatballs has violated the regulation on halal product guarantees.